Medication use review as a service for pharmaceutical care: Conditions for implementation in pharmacy practice - Żak, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Pharmaceutical care is an aggregated pharmaceutical service based on an innovative approach towards the patient’s pharmacotherapy process. It was introduced into the Polish pharmaceutical law system in 2008, but it was not until the end of 2020 that the list of activities included in this innovative health service was clarified. The delayed initiation of pharmaceutical care means that implementation procedures are lacking, making it difficult to fully implement it into pharmacy practice. The initiating service for pharmaceutical care in pharmacy practice is the medication use review (MUR), which, combined with the pharmacotherapy assessment, has the task of detecting and solving patients’ drug-related problems and thus ensuring safety in the pharmacotherapy process. Such important objectives for medication use review face organisational barriers that make its effective implementation difficult and practically impossible, limiting the scope of pharmaceutical care to the consultative aspect in practice. The aim of the article is to present the implementation conditions of medication use reviews in Polish pharmacy practice, which helped to identify the conditions for effective implementation of pharmaceutical care. Achieving the research objectives requires the use of a variety of research methods. To identify the conditions for effective implementation of medication use reviews, the method of analysis of legal acts was used. Apart from that, the analysis of literature and the method of examination of documents were also implemented, which made it possible to determine whether the Polish pharmaceutical law system creates conditions for effective provision of this service in pharmacy practice. The method of observation (the mystery shopper) was also used to indicate the territorial (subjective scope) scope of the provision of medication use review and to identify barriers to their implementation in Polish organisational and legal realities. All the methods applied made it possible to determine to what extent pharmacist shortages in the pharmacy limit the implementation process. The results of the study were subjected to statistical analysis.
Keywords: medication use review; pharmaceutical care; community pharmacy; pharmacy services; management